2020
DOI: 10.1055/s-0040-1721296
|View full text |Cite
|
Sign up to set email alerts
|

Awareness on Preventive Measures taken by Health Care Professionals Attending COVID-19 Patients among Dental Students

Abstract: Objectives Coronavirus disease is an infectious disease caused by a newly discovered coronavirus. This virus primarily spreads through droplets of saliva or discharge from the nose when an infected person coughs or sneezes. This virus was named after its shape, which takes the form of a crown with protrusions around it. The World Health Organization has recommended personal protective equipments (PPE) to doctors and health care workers attending COVID-19 patients. PPE generally includes masks, goggles, respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 30 publications
0
41
0
Order By: Relevance
“…A wide variety of pre-polymerised polymethyl methacrylate (PMMA) blocks have been introduced on the market based on further studies related with nanoparticles and data was produced on surface roughness [11]. Our team has extensive knowledge and research experience that has translated into high quality publications [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Open Accessmentioning
confidence: 99%
“…A wide variety of pre-polymerised polymethyl methacrylate (PMMA) blocks have been introduced on the market based on further studies related with nanoparticles and data was produced on surface roughness [11]. Our team has extensive knowledge and research experience that has translated into high quality publications [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Open Accessmentioning
confidence: 99%
“…Several studies have reported the success and minimal invasiveness of the preventive resin restoration as the treatment of choice for small, discrete lesions of the pits and fissures [17]. Our team has extensive knowledge and research experience that has translate into high quality publications [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. With this background, this study aims to evaluate the most commonly treated mandibular teeth with preventive resin restoration in children with mixed dentition.…”
Section: Introductionmentioning
confidence: 98%
“…The prepared surface is etched with 37% o-phosphoric acid for 15-20 seconds and the bonding agent is a applied and cured for 20 seconds, followed by restoring the cavity with filled resin and the adjacent unaffected pits and fissure is sealed using a Dental Pit & Fissure Sealant [14]. Our team has extensive knowledge and research experience that has translate into high quality publications [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%